Ski skating race technique - Effect of long distance cross-country ski racing on choice of skating technique in moderate uphill - Ardigò, L. P.; Stöggl, T. L.; Thomassen, T. O.; Winther, A. K.; Sagelv, E. H.; Pedersen, S.; Hammer, T.; Heitmann, K. A.; Olsen, O.-E.; Welde, B. (Frontiers in Sports and Active Living, 2020)
The aim of this study was to investigate the effect of prolonged ski racing using skating style on technique choice in a transition section among female and male high-level skiers. Fifty three national-to-elite level skiers (20 females: 26.7 ± 4.8 years, 167.0 ± 6.5 m, 61.0 ± 5.1 kg, and 75.5 ± 68.8 FIS points; 33 males: 25.2 ± 3.5 years, 179.0 ± 5.2 cm, 73.1 ± 5.7 kg, and 73.7 ± 63.2 FIS points) were video recorded along a flat-to-uphill transition section of a course during the 30-km (females) and 50-km (males) races at the 2018 Norwegian National Championships. Across laps, section speeds decreased (P < 0.001) in all skiers, with the best-ranked skiers faster than the lowest-ranked (P < 0.001), and males faster than females in the first and middle laps. Section speed within each lap was associated with race performance (r = 0.76-0.86, P < 0.001 in females and r = 0.87-0.89, P < 0.001 in males). The prevalence of Gear 2 (G2) increased, while Gear 3 (G3) use decreased (both P < 0.001) across the subsequent laps, with females preferring G2 more than males in lap one (P = 0.027). In long-distance skate-style skiing, transition performance is representative of race performance and skiers decrease the use of the often-faster G3 technique while increasing the use of the slower G2 technique due to prolonged exercise. Especially female skiers should consider adding some flat-to-uphill G3 practice into established training, specifically early in the session before fatigue may occur.